Antioxidant Activities of Extracts and Main Components of Pigeonpea [Cajanus cajan (L.) Millsp.] Leaves - Wu, Nan; Fu, Kuang; Fu, Yu-Jie; Zu, Yuan-Gang; Chang, Fang-Rong; Chen, Yung-Husan; Liu, Xiao-Lei; Kong, Yu; Liu, Wei; Gu, Cheng-Bo (Molecules (Basel, Switzerland), 2009)
Antioxidant activities of the aqueous and ethanol extracts of pigeonpea [Cajanus cajan (L.) Millsp.] leaves, as well as petroleum ether, ethyl acetate, n-butanol and water fractions and the four main compounds separated from the ethanol extract, i.e. cajaninstilbene acid (3-hydroxy-4-prenylmethoxystilbene-2-carboxylic acid), pinostrobin, vitexin and orientin, were examined by a DPPH radical-scavenging assay and a β-carotene-linoleic acid test. In the DPPH system, the antioxidant activity of the ethanol extracts was superior to that of the aqueous extracts, with IC50 values were 242.01 and 404.91 µg/mL, respectively. Among the four fractions, the ethyl acetate one showed the highest scavenging activity, with an IC50 value of 194.98 µg/mL. Cajaninstilbene acid (302.12 µg/mL) and orientin (316.21 µg/mL) showed more efficient radical-scavenging abilities than pinostrobin and vitexin. In the β-carotene-linoleic acid test, the inhibition ratio (%) of the ethyl acetate fraction (94.13%±3.41%) was found to be the highest, being almost equal to the inhibition capacity of the positive control BHT (93.89%±1.45%) at 4 mg/mL. Pinostrobin (>500 µg/mL) and vitexin (>500 µg/mL) showed insignificant antioxidant activities compared with cajaninstilbene (321.53 µg/mL) and orientin (444.61 µg/mL). In general, the ethyl acetate fraction of the ethanol extract showed greater activity than the main compounds in both systems, such results might be attributed to the synergistic effects of the components. The antioxidant activities of all the tested samples were concentration-dependent. Based on the results obtained, we can conclude that the pigeonpea leaf extracts may be valuable natural antioxidant sources and are potentially applicable in both medicine and the healthy food industry.